Prevalence of Major Reproductive Disorders in Canines with Reference to Age, Sex and Breed in Central Gujarat - Hadiya, Hardik D.; Patel, Dipak M.; Parmar, Jignesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A retrospective study was undertaken to assess the prevalence of various reproductive disorders attended over the last three years(2017-20) at VCC, Anand in either sex of canine. Screening of 9963 case records revealed 602 (6.04 %) cases of gynecological disordersand 23 (0.23 %) cases of andrological disorders. The highest cases in female dogs were of pregnancy diagnosis (30.89 %), followed indescending order by pyometra (25.41 %), mammary tumor (11.46 %), CTVG (7.81 %), spaying (5.65 %), pseudo-pregnancy (4.32 %),dystocia (3.32 %), vaginal prolapse (2.99 %), misalliance (2.32 %), abortion (0.99 %), normal whelping (0.49 %) and miscellaneous (3.82%). Among the male dogs, the highest cases were of venereal granuloma (21.74 %), followed by phimosis (17.39 %), balanoposthitis(13.04 %), prostate enlargement (13.04 %), scrotal edema (13.04 %), castration (8.69 %), testicular hyperplasia (4.35 %), testicular tumor(4.35 %) and orchitis (4.35 %). The breeds most prone to gynecological disorders were Labrador (29.57 %), followed by Mongrel (22.42%), Pomeranian (11.79 %), German Shepherd (11.46 %), Pug (6.64 %), Rottweiler (6.15 %), Doberman (3.50 %), Golden Retriever (3.17%), and others. Similarly, the highest occurrence of gynecological cases was found in bitches of 0-3 years age group (46.84 %), followedby 4-6 years (23.75 %), 7-9 years (14.29 %) and 10-12 years of age (11.30 %). The higher gynecological cases recorded in Labrador andMongrel breeds and in younger age groups of dogs could be due to the higher gross population of these animals in the study area ofcentral Gujarat.
Keywords: Age; Breed; Canine; Prevalence; Reproductive disorders; Sex